New results of Hominoid research in the Carpathian Basin - Kordos, László (Acta Biologica Szegediensis, 2000)
Within the dynamic tectonic realm of the Carpathian Basin five succesive primate first appearance events has documented: Griphopithecus darwini and Pliopithecus (ca. 15 M years), Dryopithecus carinthiacus (ca. 12.5 M years), Dryopithecus brancoi (= Rudapithecus hungaricus) and Anapithecus hernyaki (ca. 10 M years), Mesopithecus pentelici (between 8 and 5.5 M years), and Dolicopithecus sp.(terminal Miocene and middle Pliocene). In 1998 an associated femoral remains of adult Anapithecus were discovered at Rudabánya. RUD-184 has a large and almost perfectly spherical head, a very long, antero-posteriorly compressed neck and a robust, curved shaft with a pronounced gluteal line. A new cranium of Rudapithecus (= Dryopithecus brancoi), RUD-200 ("Gabi") were found in 1999 at Rudabánya. RUD-200 is the first Dryopithecus cranial specimen preserving large portions of the face and neurocranium with direct bone to bone contact. It shares the same great ape characters found in other Dryopithecus from Rudabánya and elsewhere in Europe (dental proportions, labiolingually thick incisors, compressed canines, elongated postcanines, no cingula, reduced premolar cusp heteromorphy, large brain, high root of zygomatic, no subarcuate fossa). It also shares African ape characters seen in other Dryopithecus specimens (laterally facing malar surface, stepped subnasal floor, mildly elongated subnasal clivus, elongated cranium, prominent entoglenoid, fused articular and tympanic temporal, subtle but distinct supraorbital torus, supratoral sulcus, projecting glabella, small but inferiorly placed frontal sinus widest at or below nasion in ethmoidal region and thin enamel with high dentine penetrance).